Kinora - Natural Lip Balm - Norashikin, Mat Zain (Faculty of Chemical & Natural Resources Engineering, 2018)
There are several brands of cosmetic in the market. However, choice-making among these brands is usually a challenge for consumers who prefer halal cosmetics. Interestingly, halal and other safe ingredients based natural tinted lip balm has been developed by Dr. Norashikin Mat Zain.